Riddle of the Talking Quill: Wandering Motives - Kensminienė, Aelita (Tautosakos darbai, 2019)
The subject of the article is an international riddle type about the quill pen, which could be provisionally entitled The Tortures of the Quill. The Lithuanian riddle of this type has over one hundred of the recorded variants, the oldest of which dates back to the beginning of the 18th century, and reads the following way: “Cut my head, take out the heart, and let me speak”. Variants of the riddle differ in terms of using the imperative vs. more neutral indicative – first or third person; frequently, they also include the fourth motive – drinking. Having accumulated all the Lithuanian variants of the riddle – both published ones and those from the archived manuscripts, as well as the international equivalents, historical sources, mythological data, folktales, legends, incantations, proverbs and proverbial sayings, the author reveals the possible connections of these riddle motives with other texts, their migration, and the religious inspirations behind them. Similar motives are discerned in the Greek myths, in the Poetic Eda, in the Western European chronicles and hagiographies describing two historical events - namely, the martyrdoms of the Saint Adalbert of Prague and the Saint Bruno of Querfurt that took place in the end of the 10th and in the beginning of the 11th century. Having surveyed all the varying motives of the riddle the author assumes that the riddle in question does not necessarily follow the descriptions of the definite historical events; rather, both the descriptions and the riddles, as well as other similar texts have been composed by adhering – whether consciously or subconsciously – to certain mythical patterns or religious events, and resonate with them. The riddle of the tortured quill may be depicting a symbolical dying that means rejecting the old nature and rebirth in a new form, having drawn from the otherworldly sources that enable one to utter the divine or prophetical words. This may also include reminiscences of the shamanic rites. Although it is not a direct transmission of a memory narrative – rather, it is more like a wandering textual memory of a once important knowledge. Various folklore texts tend to be recreated and relived from time to time, while the spread of writing signified an enormously important turning point in the human history, worth to be highlighted and emphasized. Riddles used to be an extremely important genre of folklore, related in the ancient Vedic tradition to the knowledge of the world creation and the rituals of its renewal. Such renewal could have connected the new kind of the knowledge bearer and its transmitter – i. e. the quill pen, with the shamanic rituals from the past that require particular spiritual strength and devotion to serve the common good.